Bioenergy potential of Chlorella vulgaris under the influence of different light conditions in a bubble column photobioreactor - S. Dhanasekar; R. Sathyanathan (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Recent investigations indicated that continuous use of fertilizers and pesticides in agricultural fields not only deteriorated soil health but also caused a deleterious effect on surface and groundwater bodies. Treating such wastewater using microalgae has shown higher nutrient removal and biomass efficiency. Moreover, microalgae are proven to be miniature factories that augment the huge potential of biofuel. The aim of this study is to evaluate the different light intensities required for Chlorella vulgaris algae to remove nutrients from synthetic agricultural wastewater in a fabricated bubble column photobioreactor. Additionally, the research findings focus on assessing the degradation of organic pollutants and biomass generation under different light conditions.METHODS: In this study, synthetic agrochemical wastewater was treated in a bubble column photobioreactor with blue, red, sunlight, and white light conditions. The treatment was conducted in a batch process with a hydraulic retention time of 21 days, using light intensity of 1800–2800 luminescence and a temperature maintained at 25–28° degrees Celsius.FINDINGS: Under different lighting conditions, the blue light condition exhibited a higher biomass concentration of 3.99 gram per liter, with an estimated heat energy value of 1.278 kilojoule per liter. Moreover, in the blue light condition, scanning electron microscopy analysis showed no significant changes in the shape of Chlorella vulgaris and energy-dispersive X-ray analysis elemental composition exhibited the lowest oxygen-to-carbon ratio (1.03). Fourier transform infrared spectroscopy was used to illustrate the functional group of microalgae under different lighting conditions. The lipid, protein, carbohydrate, and amino acid contents were 3329–3332, 2116–2139, 1636–1645, and 545–662 per centimeter, respectively. The higher biomass potential from the wastewater treatment shows significant benefit in terms of feedstock and biofuel production.CONCLUSIONS: The present investigation identified the nutrient reduction and biomass productivity to be more in blue light condition for Chlorella vulgaris algae. The investigation also assessed the potential of lipid, carbohydrate, and protein content in Chlorella vulgaris, which indirectly evaluates the biofuel potential of the species.